Pulse oximetry in six minutes walking test as a predictor of functional respiratory alteration in workers at artisanal coal mining - Ospina Díaz, Juan M.; Manrique Abril, Fred G.; Fernández Cely, Leidy; Roa Cubaque, Marcela; Valero Ortiz, Adriana (Universidad y Salud, 2014)
Objective: To evaluate prospectively and through comparison the behavior of the arterial oxygen saturation (SPO2) and other vital variables in two groups, one of coal miners (exposed) and another formed by university workers (controls) during the test run of 6 minutes. Materials and methods: Prospective cohort study. The test (6MWT) was performed in 72 miners and 46 university workers. SpO2, heart rate and walked distance were estimated every minute. Results: A significant oxygen desaturation was found in the mineworkers when practicing a moderate exercise, which is equivalent to an early manifestation of functional impairment of the alveolar-capillary exchange. Conclusions: The sustained respiratory exposure to coal dust and silica may cause functional impairment of alveolar capillary gas exchange. The pulse oximetry in the 6 minutes walking test is emerging as a useful and cost-effective occupational health tool to monitor and health surveillance of coal miners.